CP-191 Prescription evaluation of hospitalised patients at a district hospital, using a platform that supports antimicrobial prescription : a pilot analysis. (25th February 2017) - Capoulas, M; Palos, C; Lobo, T; Cardoso, P; Lopes, J; Marques, R; Coelho, P; Marques, E; Santos, C
Abstract : Background: A significant percentage of antibiotics worldwide are prescribed inappropriately (context, dosage and duration), especially the use of quinolones, carbapenems and anti-MRSA agents. In order to optimise interventions in a paper-free hospital, a platform has been developed locally allowing prescription monitoring and registration of multidisciplinary interventions under the platform that supports antimicrobial prescription (PAPA), complementing automatically generated email notifications when prescribing conditioned antibiotics or outside the local guidelines. Interventions are made by physician and pharmacist members of the Prevention and Control of Infection and Antimicrobial Resistance Group (GCL-PPCIRA) in real time. Purpose: To characterise hospital prescriptions for quinolones, carbapenems and anti-MRSA agents in March 2016, using the platform. Material and methods: This was a pilot prospective analysis on the use of a PAPA platform, which integrates data relating to the prescriber, scope and characteristics of the prescription, initial GCL-PPCIRA interventions, follow-up by pharmacists, medical acceptance and registration of clinical and laboratory variables. Results: The analysis involved 220 conditioned prescriptions, automatically generated by the prescription system and introduced into platform. Of these, 48% required GCL-PPCIRA interventions. 47.2% of the suggested interventions were accepted. In only 6.6% of non-accepted interventions was there an automatic justification and in 46.2% there was no given justification. Most suggested interventions (41.5%) included antibiotic exchange, suspension (26.4%), duration of therapy (12.3%), change of dosage (4.7%) and addition of another antibiotic (1.9%). Most interventions made were for carbapenems (34.9%), followed by quinolones (13.2%) and anti-MRSA agents (9.4%), with an acceptance profile, respectively, of 17/6/4 cases. 34.9% of interventions were made in the emergency department. Conclusion: In order to reduce the emergence of resistances, conducting interventions under a PAPA should be complemented by evaluation of prescription quality and adequacy of interventions, requiring tools that integrate information and enable real time interventions by multiple professionals. This analysis concluded that the rate of interventions in total prescriptions generated meets the estimated international values, which translates into a good robustness. The data analysis related to the reasons for interventions and acceptance rate, and other data not mentioned in this analysis, makes it possible to define improvement strategies for good antibiotic prescribing practices, particularly in the conditioned antibiotics from the prescriber to the institutional level. No conflict of interest